Eulogy for burying a crane and the art of Chinese calligraphy - Xue, Lei, 1975- (University of Washington, 2019)
"Eulogy for Burying a Crane (Yihe ming) is perhaps the most eccentric piece in China's calligraphic canon. Apparently marking a burial of a crane, the large inscription, datable to 514 CE, was once carved into a cliff on Jiaoshan Island in the Yangzi River. Since the discovery of its ruins in the early eleventh century, it has fascinated generations of scholars and calligraphers and has been enshrined as a calligraphic masterpiece. Nonetheless, skeptics have questioned the quality of the calligraphy and have complained that its fragmentary state and worn characters make any assessment of its artistic value impossible. Moreover, historians of calligraphy have trouble fitting it into their storyline. Such controversies illuminate moments of discontinuity in the history of Chinese calligraphy that complicate the mechanism of canon formation. In this volume, Lei Xue examines previous epigraphic studies and recent archaeological finds to consider the origin of the work in the sixth century, and then traces its reception history after the eleventh century, suggesting that formation of the canon of Chinese calligraphy over two millennia has been an ongoing process that is embedded in sociopolitical realities of particular historical moments. This biography of the stone monument Eulogy for Burying a Crane reveals Chinese calligraphy to be a contested field of cultural and political forces that have constantly reconfigured the practice, theory, and historiography of this unique art form"--